Analysis of the use of mother and child health (mch) books by pregnant women in controlling stunting in the working area of Koto Baru community health center, Kuantan Singingi District - Riski Novera Yenita; Rifa Yanti; Sandra Febriani; Romi Mulyadi (Riset Informasi Kesehatan, 2022)
The Maternal and Child Health Book (KIA) contains important information needed by mothers and children,The low utilization of the MCH handbook is still constrained by the lack of knowledge about the benefits of the MCH handbook and some mothers also think that the MCH handbook is just an examination notebook..Koto Baru Health Center is one of the health centers in the districtKuantan singingi whose KI coverage reaches 100%. The high coverage of K1 is not in line with the use of MCH books by pregnant women.This research aims to knowing determinants related to the use of Maternal and Child Health (KIA) books by pregnant women in stunting control in the Koto Baru Health Center Work Area, Kuantan Singingi Regency. Types of research quantitative research with analytical research design and using a cross sectional approach. The sample was taken by total sampling technique with a sample of 36 respondents. Data were analyzed by univariate and bivariate.Research results obtained respondents used the MCH book well (61.1%), highly knowledgeable (63.9%), positive perception (52.8%), received family support (55.6%) and received the role of health workers (72, 2%). The results of the chi square test showed that there was a relationship between knowledge (p = 0.002), perception (p = 0.001), family support (p = 0.003) and the role of health workers (p = 0.001)with the use of Maternal and Child Health books. Kepada Health workers to improve services such as provide counseling, promotion and continuous information to pregnant women about the contents of the MCH handbook and its benefits for mothers and children so that pregnant women know the condition of their pregnancy and immediately check with health workers if they experience problems in pregnancy.